Technical-locomotor proficiency gaps in youth badminton beginners: serve, net-drop, smash, and footwork - Maulidia Putri; Eval Edmizal; Tjung Hauw Sin; Juanda Putra (Indonesian Institute For Counseling, Education and Therapy, 2026)
Technical competence is essential for long-term athlete development in badminton; however, the development of racket skills and court-movement abilities during the novice stage remains insufficiently examined. This study aimed to describe serve, net-drop, and smash accuracy, as well as footwork agility, and to examine their relationships with chronological age and sex. A descriptive quantitative, cross-sectional design was employed involving 23 novice athletes (16 boys and 7 girls) aged 11–15 years from a university-affiliated badminton academy in West Sumatra, Indonesia. Participants completed a standardized field-test battery consisting of a modified French-Scott-Fox serve accuracy test, net-drop and smash accuracy tests, and an 8-point footwork agility test. Data were analyzed using descriptive statistics, norm-referenced scoring, Spearman’s rank correlation, and the Mann–Whitney U test. Mean serve accuracy was 45.4% (SD = 22.3), while net-drop and smash accuracy scores were 21.52 (SD = 8.55) and 18.74 (SD = 9.66), respectively. Mean footwork time was 18.14 s (SD = 3.33), with 69.6% of athletes classified in the very slowest normative category. Racket skills demonstrated moderate-to-high intercorrelations (ρ = 0.60–0.69, p < 0.01), whereas footwork was significantly correlated only with smash accuracy (ρ = −0.49, p = 0.018). Boys outperformed girls across the four performance measures (p = 0.006–0.007; d = 1.10–1.19), despite no significant difference in age distribution (p = 0.397). Age showed moderate-to-strong associations with the measured skills (|r| = 0.47–0.57, p < 0.03). These findings indicate that racket-handling and locomotor skills represent relatively distinct domains of early technical development. Therefore, novice training programmes should place greater emphasis on footwork and multidirectional agility while considering age- and sex-related differences when grouping athletes for training.